Production characteristics of a herd of East African Mubende goats - Sacker, G.D.; Trail, J.C.M. (1966)
Production characteristics covering female breeding data; growth of kids and use of correction factors for parity of dam, sex and type of bith of kid; dam milk production as measured by early kid growth; repeatabilities and phenotypic correlations between kid weights; and kid mortality, were examined in a herd of East African Mubende Goats maintained over an eight-year period in Western Uganda. The age of females at first kidding was 567±11.6 days and the mean overall kidding interval was 296.7±8.5 days. Twinning occurred in 30 percent and triplets in 1.7 percent of births. An average of six kid crops per female were produced over the period from birth to 5-6 years of age. Kid weight correction factors were worked out for parity of dam, sex and twinning; the mean weights of male single kids were 4.7±0.1 lb (2.1±0.04 kg) at birth, 16.2±0.41lb(7.35±0.2 kg) at two months, 26.2 ± 0.6lb (11.9±0.3 kg)at weaning and 44.7 ± 0.9 lb (20.3±0.4 kg)at one year. Milk production, as measured by early kid growth, was not significantly greater in second and subsequent kidding females than in first kidding females; females rearing twins produced significantly more than females rearing singles, although the mean daily gain of individual twin kids was significantly lower than that of single kids. No repeatability values were significant. The correlations between kid body weights at different ages showed birth weight to have little effect upon subsequent body weights, two month weight to be a useful guide to weaning weight, and weaning weight to be of some value in predicting weight at one year. The overall mortality rates to weaning were 18.8 percent for singles from second and subsequent kidding dams, 45.3 percent for singles from first kidding dams and 36.1 percent for twins from second and subsequent twining dams. Current plans for the introduction of Toggenburg blood for improved production were mentioned.